1996
DOI: 10.1016/s0895-7061(96)00257-9
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes may synthesize their own nitric oxide

Abstract: The ability of hemoglobin and myoglobin to bind nitric oxide (NO) produced by other cells and circulating vasodilators is well known. To characterize erythrocytes (RBCs), we used NADPH diaphorase labeling, as well as antibodies to the three known types of NO synthase (NOS 1, 2, and 3), and to a molecule usually associated with NOS, calmodulin. We show that the NADPH-diaphorase label labels myenteric neurons, endothelial cells, and the blood cells trapped in the lumen of the blood vessels running through the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Two earlier studies suggested that RBCs also contain iNOS. 20,25 We are unable to confirm these reports as we failed to isolate any iNOS from crude human RBC lysates of healthy donors using specific anti-NOS2 antibodies for immunoprecipitation.Although a L-NNA/L-NAME-inhibitable NOS activity was demonstrated by measuring NO metabolites or citrulline in the supernatant of intact erythrocytes 2,15,16,19 and RBC membranes,16,23 2 reports suggested RBCs harbor an inactive NOS. 20,22 It was important to confirm, therefore, that the protein identified as eNOS in our study was catalytically active, L-arginine:citrulline conversion was dependent on the presence of Ca 2ϩ /calmodulin, and activity was inhibited by L-NAME.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Two earlier studies suggested that RBCs also contain iNOS. 20,25 We are unable to confirm these reports as we failed to isolate any iNOS from crude human RBC lysates of healthy donors using specific anti-NOS2 antibodies for immunoprecipitation.Although a L-NNA/L-NAME-inhibitable NOS activity was demonstrated by measuring NO metabolites or citrulline in the supernatant of intact erythrocytes 2,15,16,19 and RBC membranes,16,23 2 reports suggested RBCs harbor an inactive NOS. 20,22 It was important to confirm, therefore, that the protein identified as eNOS in our study was catalytically active, L-arginine:citrulline conversion was dependent on the presence of Ca 2ϩ /calmodulin, and activity was inhibited by L-NAME.…”
mentioning
confidence: 84%
“…RBCs contain both a constitutive Ca 2ϩ -dependent NOS containing epitopes of an eNOS 6,15,16,25 and an active XOR. 6 Thus, enzymatic NO synthesis in RBCs might occur either via NOS-catalyzed L-arginine to citrulline conversion 15,16,18 or by XOR-mediated nitrite reduction.…”
Section: Origin Of Constitutive No Synthesis Within Rbcsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Red blood cells, although lacking a nucleus, are useful models for membrane transport studies 34,35 and share membrane properties related to VSMC and the endothelium. RBC, which are equipped with IK Ca and inducible nitric oxide synthase, 36,37 respond to K Ca activators producing vasodilatation 7 or to 8Br-cGMP (Delgado et al, 2002, unpublished data) in a manner similar to the VSMC with the activation of K Ca and the efflux of K + . 8 Consequently, K + changes in RBC could be a marker for K + changes in other cells such as VSMC and the endothelium.…”
Section: Discussionmentioning
confidence: 99%